(untitled) (City: History, Culture, Society, 2017)
The article is devoted to the created in the Park «Kyian Rus» Museum of Wooden Architecture. The reader can get acquainted with this unique phenomenon in the modern museum world as a project restoring ancient Kyiv («city of Vladimir») in 1: 1 scale. Modern experience supply objective information and historical reconstructions (individual subjects, objects, and even entire urban locations) include providing opportunities to experience the atmosphere and the specifics of Kievan Rus in all its fullness. The perfect opportunity to achieve this is a reproduction of the image of the medieval city, but not on the monitors and models, but as in the original. Experience of the solution to the problem is a museum complex in the open air - «Park Kievan Rus». Today we can confidently assert that the ambitious project of PKR to reproduce the ancient capital grew to a powerful research center, which deals with a wide range of problems associated with medieval history, archaeology, and museology. The author presents the basic features of the museum complex areas - reconstruction and construction of fortifications and sacral buildings, housing and commercial complexes, street network planning and other constants medieval city. One of the scientific and educational activities PKR is the creation of museums on its territory. One of these new museums - the Museum of Wooden Architecture. The museum is unique because it exhibits archaeological artifacts, reconstructed models of ancient structures housing, replicas of ancient tools of the carpenter. According to archeological data, the main types of woodworking tools and their range took constant shape in the X - XI and remained unchanged until the XVIII century. The exhibition features tools that can be considered replicas of ancient counterparts, their identity is proven by archaeological artifacts. The basis of the comparative analysis underlying the development of V. Kharlamov. Among the exhibited things can be identified replica tesla, boats, planes, drills, saws, hammers and others. Archaeological studies in recent years finally convince us wide distribution in Old Kyiv namely carcass type residential buildings. Therefore, third mainline presents the reconstruction of some ancient frame, frame layout design method vrubky «v oblo», layout windows and roof of the home.